2018
DOI: 10.1073/pnas.1714512115
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine prevents relapse and produces long-term complete remissions in leukemia xenografts treated with Moxetumomab pasudotox

Abstract: Moxetumomab pasudotox (Moxe) is a chimeric protein composed of an anti-CD22 Fv fused to a portion of exotoxin A and kills CD22-expressing leukemia cells. It is very active in hairy-cell leukemia, but many children with relapsed/refractory acute lymphoblastic leukemia (ALL) either respond transiently or are initially resistant. Resistance to Moxe in cultured cells is due to low expression of diphthamide genes (DPH), but only two of six ALL blast samples from resistant patients had low DPH expression. To develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…However, reduced diphthamide synthesis gene expression was also observed in immunotoxin-responsive patient cells. It was concluded that diphthamide gene expression could not account for the majority of resistant cases [ 54 ]. Mouse models injected with GFP/luciferase-expressing KOPN-8 or Reh cells revealed that a few resistant cells persisted in the bone marrow and subsequently expanded systemically.…”
Section: Inhibition Of Protein Synthesis (Step 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduced diphthamide synthesis gene expression was also observed in immunotoxin-responsive patient cells. It was concluded that diphthamide gene expression could not account for the majority of resistant cases [ 54 ]. Mouse models injected with GFP/luciferase-expressing KOPN-8 or Reh cells revealed that a few resistant cells persisted in the bone marrow and subsequently expanded systemically.…”
Section: Inhibition Of Protein Synthesis (Step 3)mentioning
confidence: 99%
“…Significant chromosomal alterations were also observed. Interestingly, 5-azacytidine prevented this resistance in one mouse model and delayed it in another, though it was unable to overcome established resistance [ 54 ].…”
Section: Inhibition Of Protein Synthesis (Step 3)mentioning
confidence: 99%
“…The fact that dormancy and resistance are reversible upon release from the microenvironment indicates that transcriptional reprogramming of ALL-LIC is an early event in the generation of therapy resistance. This process may precede the onset of hardwired irreversible resistance and relapse, and a similar multistep-mechanism of the emergence of resistant disease has recently been suggested under treatment with the immunotoxin Moxetumomab pseudotox [109]. The in vivo model described in our recent study [68], in combination with CRISPR-Cas9 edited NGS mice [91] can facilitate dissecting regulatory factors within the bone marrow microenvironment that endow LIC with adverse characteristics.…”
Section: Functional Characterization Of Lrc In All-pdxmentioning
confidence: 82%
“…Therefore, it is possible that resistance mechanisms may be shared across this class of toxin immunoconjugates. However, while in vitro resistance to moxetumomab pasudotox in cell lines was associated with downregulation of diphthamide synthesis pathway genes (21), this did not seem to be the dominant mechanism of resistance in B-ALL treated in vivo (30). Rather, moxetumomab resistance was associated with a developmental state change, karyotypic abnormalities, and loss of surface CD22 expression.…”
Section: Cell Linesmentioning
confidence: 99%
“…Rather, moxetumomab resistance was associated with a developmental state change, karyotypic abnormalities, and loss of surface CD22 expression. Yet, despite this difference, azacitidine and moxetumomab were also an effective combination in B-ALL cell lines treated in vivo (30). Thus, mechanisms of in vivo resistance to diphthamide-targeting toxins may be disease or celltype dependent.…”
Section: Cell Linesmentioning
confidence: 99%